Detection of spindle thermal state accuracy of vertical CNC machine tool. (15th August 2019) - Wang, Jianchen; Deng, Xiaolei
In order to test the thermal accuracy of spindle system of mining vertical CNC machine tools, to enhance the error compensation ability of the system accuracy detection model and improve the machine tool processing accuracy, a test platform for thermal accuracy of spindle system was constructed. Five-point method was used to test the thermal accuracy of spindle system, and thermocouple and infrared thermal imager were used to measure the spindle system. Temperature change data at key points of temperature rise are used to identify temperature sensitive measurement points by grey comprehensive correlation analysis method. A thermal accuracy prediction model based on cooperative quantum particle algorithm is constructed. The prediction effect of the model is evaluated. The experimental results show that the thermal accuracy detection model has high detection accuracy.